ASSESSMENT OF THE DEGREE OF SOIL CONTAMINATION OF THE COASTAL ZONE OF THE CASPIAN SEA IN THE AREA OF AKTAU SUBURB (Eurasian Journal of Ecology, 2023)
The article presents an assessment of the degree of soil contamination of the coastal zone of the Caspian Sea in the suburbs of Aktau. It examines the content of heavy metals at research sites in 2021 compared to 2018. The studies were conducted in the period from April 18 to April 25, 2021. Samples were taken according to a well-known method in soil science, at a depth of 0-20 cm by the envelope method using a sampler. The determination of humus in soil samples was carried out using the Nikitin method with a colorimetric ending by Orlov-Grindel. Mobile forms of heavy metals were determined at research sites using an atomic absorption spectrometer (MGA-915). According to the results of the research, it was revealed that the soils of the surveyed territory differed in the alkaline reaction of solutions, the content of organic matter at a low level and low resistance to anthropogenic influences. The content of heavy metals such as cadmium, arsenic and nickel decreased in 2021. It was found that the values of cadmium in all samples have the same values, and the values of arsenic are reduced. During the comparison, it was found that these results have not changed much, and the decrease in the content of heavy metals in the soil indicates a decrease in the anthropogenic load on the environment, due to the suspension of activities in all areas during the pandemic.Keywords: monitoring, soil, pollution, heavy metals, Caspian Sea, coastal zone, soil analysis.